PENERAPAN METODE RAD UNTUK PENGEMBANGAN SISTEM PENGELOLAAN DATA KEPEGAWAIAN - T. Tanzil Azhari Risky; Armansyah (Yayasan Pendidikan Cahaya Budaya Indonesia, 2026)
Employee data management at the Medan Religious Training Center includes personal data, employment documents, educational history, work history, performance, and family data, requiring an integrated system for fast and accurate recording, updating, and reporting. This study developed a web-based Personnel Management Information System using the Rapid Application Development (RAD) method through needs analysis, prototyping, user evaluation, and implementation. Research data was obtained through observation, interviews, SOP document studies, and user questionnaires. The results showed that the system was able to integrate all personnel data, provide verification features, and generate PDF and Excel reports. Black Box testing of 10 main functions showed a 100% success rate with an average score of 5.0 (category “Very Good”). The system is considered feasible and effective in improving the efficiency and accuracy of personnel data management at the Medan Religious Training Center.